Treatments of sleep bruxism in children: A systematic review and meta-analysis. Issue 1 (2nd January 2021) - Ierardo, Gaetano; Mazur, Marta; Luzzi, Valeria; Calcagnile, Francesca; Ottolenghi, Livia; Polimeni, Antonella
ABSTRACT: Objective : Treatment of sleep bruxism (SB) in children is not well established. The aim of this study was to develop evidence-based recommendations on SB therapy in children between the ages of 2 and 17. Methods : A systematic review and meta-analysis was conducted. Literature searches were performed using MedLine (PubMed), Web of Science, Scopus, and the Cochrane Library (November 30 2017). Results : The search strategy identified 268 potential articles; 10 papers were included in the qualitative synthesis and 3 in the meta-analysis, for a total of 94 patients. Hydroxyzine therapy showed the strongest efficacy on SB (OR 10.63; CI 95%, 1.48 to 76.08). Flurazepam and Melissa officinalis therapies presented lower grades of association with decreased SB symptoms. Conclusions : Data on treatments of SB in children are limited. Future studies with a proper design, conducted on a meaningful number of patients, and based on standardized and developed diagnostic criteria are desperately needed.